Tobacco (Nicotiana species) research in India - progress, problems and prospects - LAXSHMINARAYANA, R (The Indian Journal of Agricultural Sciences, 2013)
In tobacco (Nicotiana spp) introduction and acclimatization of exotics in flue-cured virginia and isolation of purelines from local cultivars in non-virginia type took place during the early phase (forties-sixties) of varietal development. Later with changing requirement of trade and consumer, a number of suitable breeding programmes were formulated to develop superior varieties with high yield, quality and resistance to disease, pest and drought. The crop earns about Rs 4 500-5 000 million foreign exchange and about Rs 40 000 million central excise revenue annually to the national exchequer. However, during 1996-97 it showed an upward movement of Rs 7 000 million foreign exchange. Tobacco industry comprising cigerette and bidi Sectors contributed 6.54 million jobs with a generation of total income of Rs 126 300 million during 1994-95. Consumption pattern in our country indicates that cigarettes represent only 18% of tobacco consumption by weight, bidis a large share of 55% and chewing tobacco snuff etc 27%. The article deals with the progress made in the crop improvement in different types of tobacco, development of disease- and pest-resistant varieties, crop production, crop protection, crop chemistry and quality. Problems and prospects of the crop are also covered.